Enhancement of Rice Yield Through Introgression of Drought Tolerance QTL in Swarna Sub 1 (Oryza sativa L.) Using MAS Based Approaches - Sureshrao, Sonam Kale; Rameshsing, Chavan Narendra; Pradeeprao, Kadu Tanvi; Prasad, Archana; Verulkar, S. B. (International Journal of Bio-resource and Stress Management, 2023)
Rice is a highly drought sensitive crop, and most semi-dwarf high yielding varieties suffer severe yield losses from reproductive stage drought stress in Chhattisgarh. In Chhattisgarh, rice variety swarna sub1, covers major area is the most popular high yielding variety in central India, however is susceptible to water stress (Drought), which is quietly frequently occurs in recent past leading to significant yield losses. We studied 10 yield contributing physiological traits under irrigated, and terminal stage drought (TSD) conditions in F2 and F3 progenies derived from the crossed of swarna sub1 (Drought susceptible) and IR 84984-83-15-159B (Drought tolerant). Genotypic study was done using peak primers/markers for targeted region on chromosome 12 to know the presence of qDTY 12.1 in swarna sub1 lines which were resistant to drought stress. The molecular marker analysis revealed that polymorphic markers RM511, RM1261, RM28130, RM7195 and RM28099 shows significant association with different yield contributing physiological traits. Out of these markers the marker RM511, RM1261 and RM28130 were significantly associated with grain yield under TSD condition. Statistical analysis for the PCV and GCV revealed that in both the conditions i.e. irrigated (control) and Terminal stage drought (TSD), the estimates of phenotypic co-efficient of variation (PCV) were higher than the corresponding estimates of genotypic co-efficient of variation (GCV) for all the traits/characters. Association of phenotypic and genotypic data revealed that line number 4, 21, 28, 32, 35, 36 and 37 were co-segregated with polymorphic markers and these lines were similar to the swarna sub1 morphologically with QTL 12.1 having drought tolerance.